Interpretative processes and meaning construction in virtual communicative space - Aziza Arslonovna, Muminova; Mukhlisa Sharof kizi, Rasulova (The Lingua Spectrum, 2026)
This article analyzes the specific features of interpretive processes and the main principles of meaning construction in virtual communication spaces through a systematic analysis of survey results. The study focuses on how meaning is formed from a pragmatic perspective in digital communicative environments, emphasizing the important role of context, participant-related factors, and multimodal media in the interpretation of communicative units. Particular attention is paid to the dynamic and constructive nature of meaning, emphasizing that meaning is not fixed or static, but is constantly formed and transformed in the course of discourse. The study explores how virtual interactions shape understanding through linguistic, social, and technological dimensions. The empirical part of the article is based on survey results that represent diverse interpretations of speech units in virtual communication, demonstrating how pragmatic factors contribute to meaning-making processes. By exploring these mechanisms, the research provides a deeper understanding of how individuals negotiate, interpret, and construct meaning in technologically mediated spaces. The findings contribute to broader discussions in pragmatics, discourse analysis, and virtual communication studies by offering a clearer understanding of communication practices in contemporary digital contexts.